PREPARATION AND IN-VITRO ESTIMATION FOR GASTRORETENTIVE FLOATING HOLLOW – MICROSPHERES OF FAMOTIDINE - NEHA SINGH,; SHIVAKUMAR HN,; AVICHAL KUMAR, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present study’s objectives were to prepare and evaluate gastroretentive floating hollow-microspheres (HM) of the selected Famotidine (FM) to enhance its retention time within the stomach. Methods: HM was prepared by solvent emulsion diffusion technique utilizing various polymers such as ethyl cellulose, eudragit L100, eudragit S100 as polymers, and Dichloromethane and methanol as solvents. The formulated HM was estimated for their particle-size, entrapment efficiency, floating ability, scanning electron microscopy, and in vitro drug release of drug. Results: The average particle-size of the formulated HM was within the range of 262.3±3.5 to 323.1±2.1μm. The SEM confirmed the smooth surface, sphere shape, and hollow cavity within it. The formulated microspheres showed good floating behavior for up to 8 h because of their low particle size. The invitro release profile of the HM displayed a controlled-release of FM microspheres in pH1.2 for up to 8 h. Conclusion: The result depicts that the formulated HM of FM by virtue of good floating time and sustained release properties is likely to improve the retention time within the stomach and thereby the oral bioavailability.